El origen y protagonismo de la masonería en Michoacán, 1821-1831 (Tzintzun, Revista de Estudios Históricos, 2016)
he study of social skills is a research area in which cultural, as well as politicaland social history are intertwined. Within this ield, we can distinguishthe speciic subject of the emergence, settling and impact of Freemasonryin Mexico during the last two centuries. In the present paper, the presenceof such groups will be looked at in the state of Michoacán at the beginningof the independent period, through the “York” and “Scottish” lodges. Manymembers of renowned groups of political power used these lodges as a protestspace. hey debated and manoeuvred around the organizational models thatthey considered suitable for Mexico from their respective individual and collectivepoints of view and expectations. his paper presents a prosopographicaloutline of the most representative members of the federalist-liberal andcentralist-conservative coalitions, which at the same time supported theselodges, even ater their formal ban by the federal government in the autumnof 1828. he study will emphasize their force correlations and their respectivenetworks.
Keywords: Freemasonry; lodges; Valladolid; Morelia; Michoacán